JOJO MOYES’ NOVEL "TILL I MEET YOU" AS AN ARTISTIC UNDERSTANDING SPIRITUAL TRANSFORMATION HERO - Terekhovska, Olena; Chorna, Tetiana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article examines the problem of spiritual transformation in Jojo Moyes’ novel "Me before You" in theoretical and overview aspects. Within the framework of the topic, the definition of spiritual transformation is clarified, its key aspects are described. It is shown that in literature, spiritual transformation is realized through literary heroes, with whom an internal evolution occurs, leading to a reassessment of values, a change in worldview or moral rebirth. It is found that in the artistic discourse of postmodernism, in particular in the novels of Jojo Moyes, the spiritual transformation of characters reflects the psychological depth and multidimensionality of the personality. Characters, through crisis situations, losses and the search for the meaning of life, undergo a process of internal changes, form integrity, the ability to self-knowledge and harmonious interaction with society. It is proven that personal spiritual transformation in Jojo Moyes’ novel "Me before You" acts as a central artistic concept, organically combining plot events and moral and philosophical issues of the work. The changes that the main characters undergo concern not only their emotions and behavior, but also their worldview, values, inner freedom and responsibility. It has been found that the postmodernist spiritual transformation fully corresponds to the artistic and aesthetic canons of this direction and is characterized by a transition from monolithic ideologies and objective truth to pluralism, irony, and deconstruction of traditional values